Wrapped and strapped eaudiobook - James, Lorelei (Blacktop Cowboys, 2015)
Flower child, vegetarian, and humanitarian Harlow Pratt and gruff cattle ranch foreman Hugh Pritchett have been taunting each other for years. Hugh thinks that she's nothing but a spoiled rich girl, and he's had enough of that life with his ex-wife. Harlow thinks that Hugh is an ill-mannered troublemaker who wouldn't know fun if it bit him on his tight, denim-clad butt. When Harlow and Hugh are forced together at the Split Rock Ranch and Resort, everything changes. They might be polar opposites, but working out their differences skin to skin, in the dark, seems to help them find some common ground. But when trouble from both their pasts comes calling, Harlow and Hugh have no one else to lean on. Can they trust one another enough to make it through the hard times together, or will their tentative truce fall apart? Contains mature themes.